2017
DOI: 10.1016/j.vaccine.2016.11.085
|View full text |Cite
|
Sign up to set email alerts
|

A commercial porcine circovirus (PCV) type 2a-based vaccine reduces PCV2d viremia and shedding and prevents PCV2d transmission to naïve pigs under experimental conditions

Abstract: Porcine circovirus type 2 (PCV2) vaccination has been effective in protecting pigs from clinical disease and today is used extensively. Recent studies in vaccinated populations indicate a major PCV2 genotype shift from the predominant PCV2 genotype 2b towards 2d. The aims of this study were to determine the ability of the commercial inactivated PCV2a vaccine Circovac® to protect pigs against experimental challenge with a 2013 PCV2d strain and prevent transmission. Thirty-eight pigs were randomly divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 40 publications
2
50
0
1
Order By: Relevance
“…While the efficacy of currently available PCV-2a-based commercial vaccines to protect against clinical sign onset was demonstrated in several experimental trials [30,35,36], differences have been highlighted in terms of immune response and viremia. In fact, homologous vaccines can guarantee a better (or complete) viremia control and higher neutralizing antibodies [31,37,38] compared to heterologous ones. PCV-2 vaccines have sometimes been considered a "leaky vaccine" [36], meaning they tend to decrease transmission and infection rates in controlled situations such as in a vaccine trial or in the presence of good farm conditions, but they may not confer full protection under conditions of repeated exposure and in the presence of other cofactors [39].…”
Section: Discussionmentioning
confidence: 99%
“…While the efficacy of currently available PCV-2a-based commercial vaccines to protect against clinical sign onset was demonstrated in several experimental trials [30,35,36], differences have been highlighted in terms of immune response and viremia. In fact, homologous vaccines can guarantee a better (or complete) viremia control and higher neutralizing antibodies [31,37,38] compared to heterologous ones. PCV-2 vaccines have sometimes been considered a "leaky vaccine" [36], meaning they tend to decrease transmission and infection rates in controlled situations such as in a vaccine trial or in the presence of good farm conditions, but they may not confer full protection under conditions of repeated exposure and in the presence of other cofactors [39].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Opriessnig et al [ 46 ] reported that the current PCV2 vaccines, which were developed based on PCV2a, can prevent PCV2d transmission to naive pigs and the vaccinated pigs showed reduced levels of PCV2d viraemia. Because mass vaccination with PCV2a-based inactivated vaccines are applied to 3–4-week-old piglets and sows in Korean farms, it was concluded that the current PCV2 vaccines reduce clinical symptoms and lesions caused by PCV2d but do not provide sterile immunity against PCV2d infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, experimental evidence from the controlled studies also supported that a viremia was effectively decreased by homologous vaccine more than heterologous vaccine in a concurrent PCV2a and PCV2d challenge [21]. Besides, viremia and shedding of virus were still observed in PCV2avaccinated pigs, although the viral load was decreased after the PCV2d challenge [22], which was observed from the studies using challenging viruses of other genotypes [12,[22][23][24]. Moreover, mutant PCV2b (PCV2d) was isolated from vaccinated farms [4,10].…”
Section: Discussionmentioning
confidence: 83%